ICC 2019 - 2019 IEEE International Conference on Communications (ICC) 2019
DOI: 10.1109/icc.2019.8761447
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coherent Multiuser Massive MIMO-OFDM with Differential Modulation

Abstract: Massive multiple-input multiple-output (MIMO) and orthogonal frequency division multiplexing (OFDM) are wireless technologies adopted by the Fifth Generation (5G) of mobile communications. The channel estimation and pre/postequalization processes in coherent detection schemes for massive MIMO-OFDM are a challenging task, where several issues are faced, such as pilot contamination, channel calibration, matrix inversions, among others. Moreover, they increase the energy consumption and latency of the system. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(64 citation statements)
references
References 10 publications
0
64
0
Order By: Relevance
“…We will use the frequency domain implementation of the NCDS presented in [16]. This method has the advantage of involving a lower processing delay.…”
Section: Non-coherent Demodulation Scheme (Ncds)mentioning
confidence: 99%
See 4 more Smart Citations
“…We will use the frequency domain implementation of the NCDS presented in [16]. This method has the advantage of involving a lower processing delay.…”
Section: Non-coherent Demodulation Scheme (Ncds)mentioning
confidence: 99%
“…On the other hand, NCDS is suitable for these extreme cases where resources are not wasted to transmit reference signals. Indeed, [14]- [16] showed that NCDS has a great robustness against high Doppler scenarios, no matter the delay spread when OFDM is used. On the contrary, for low mobility or fixed communication scenarios with low or moderate values of delay spread, the number of reference signals can be greatly reduced ( ↓ and ↓) since the channel remains quasi-static in both dimensions.…”
Section: Throughput Evaluation For Different Channel Scenariosmentioning
confidence: 99%
See 3 more Smart Citations